States and citizens accommodation, facilitation and resistance to globalization - Shefner, Jon, 1958- (Bingley, U.K. : Emerald, 2015)
Globalization has been subjected to a variety of analyses over the past thirty years, ranging from examinations of homogenizing cultural trends to the pressures of economic austerity and trade relations to the declining influence of states. This volume examines how states and citizens have been able to address globalization in different ways across the Global North and South. Authors examine the state as it forms policies in agro-production, contends with critical constituencies, and rebuilds capacity to act in the popular interest after forty years of neoliberal assault. Other contributors discuss citizen choices in the face of global markets as divergent as food, tourism, and pharmaceuticals, and examine the global reach of human rights efforts. This volume pushes forward theoretical understandings of how concrete institutions express agency even in the face of what seems like monolithic and inevitable structures of globalization. The actions taken by states and citizens further inform us about how globalization can be further shaped in the pursuit of social justice.
Introduction : mid-level theorizing on macro structures : globalization, states, and citizen action / Jon Shefner -- Fostering consent in a post-Fordist regime : the case of industrial maize farming in Turkey / Yetkin Borlu, Leland Glenna -- Pharmaceutical autonomy : technology, alliances, and norms / Matthew B. Flynn -- Palm oil expansion in Indonesia : land grabbing as accumulation by dispossession / Paul K. Gellert -- Situating the green economy : discourses, cooptation, and state change / Jenna A. Lamphere, Jon Shefner -- The state in context : Latin America's new left and the legacies of the state / Aaron T. Rowland -- Racial neoliberalism in Costa Rican tourism : Blanqueamiento in the twenty-first century / Michelle Christian -- Contested landscapes : collaborations between displaced communities and international advocacy groups in Guatemala / Eliza Guyol-Meinrath -- Rural gentrification and growing regional tourism : new development in South Central Appalachia / Rhiannon A. Leebrick -- Globalization and the agrarian question : divergent development of two export-oriented farming communities / Rachel Soper -- Gently biting the hand that feeds : popular engagement with economic inequality after the great recession / Cory Blad.
Print version record
Keywords: Social Science -- Sociology -- General; Political Science -- Globalization; Social theory; Globalization; Shefner, Jon; Globalization -- Social aspects